Warmer temperatures result in maladaptive learning of sexual preferences. (10th January 2023) - Holveck, Marie‐Jeanne; Muller, Doriane; Visser, Bertanne; Timmermans, Arthur; Colonval, Lidwine; Jan, Fabrice; Crucifix, Michel; Nieberding, Caroline M.
Abstract: The impact of learning ability and sexual selection on the climate and biodiversity crisis is currently unclear. Using the African butterfly Bicyclus anynana, which shows strong phenotypic plasticity (i.e., polyphenism) in response to temperature, we tested whether learning affects mate preferences under climate warming. We first modelled climate warming scenarios and then showed experimentally that temperature becomes an unreliable cue to the onset of the dry season, adult butterflies displayed the wet season rather than the dry season form. Experienced females that were exposed to different male seasonal phenotypes during sexual maturation changed sexual preferences. Female fertilization success was reversed for naive compared with experienced females, likely reducing female fitness following climate warming. Our results emphasize the importance of sexual selection, learning, and their fitness consequences for understanding (mal)adaptation of natural populations to climate warming. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.